Cross-sectional analysis of university technology commercialization initiatives - Burns, Michael Owen (Kansas State University, 2008)
The promulgation of the Bayh-Dole Act of 1980, a declining share of federal research expenditures to the university, and the enforcement of intellectual property rights have contributed to the evolution of university research missions. This thesis sought to understand how the intellectual property policies and commercialization initiatives at research universities affect their commercialization activities and intensity. The ability of universities to engage in commercialization activities is dependent on the willingness of the researchers to disclose their inventions. We used cross-sectional data from AUTM (Association of University Technology Managers) and other sources to evaluate the effect universities intellectual property policies and other factors on faculty willingness to disclose their inventions and discoveries. The research revealed that universities' commercialization efforts have been intensifying over the years and across the institution. Intellectual property policies were found to have insignificant effect on the number of disclosures. This supports earlier research that has shown many faculty members were ignorant about such policies. On the other hand, licensing revenue, which basically goes to fund future research, was a very significant factor in disclosures and hence commercialization initiatives at universities.
Keywords: Intellectual Property; Cross-Sectional; Commercialization; Technology Transfer; Economics, Agricultural (0503)